A Pleasure That Hurts: The Ambiguous Effects of Elite Tutoring on Underprivileged High School Students - Ly, Son Thierry; Maurin, Eric; Riegert, Arnaud (Journal of Labor Economics, 2020)
This paper reports findings from a randomized evaluation of an intensive tutoring program conducted in underprivileged high schools. Within each school, the intervention targets students identified as having the ability to pursue a college education. The program is designed to strengthen their readiness for higher education. We demonstrate that such an intervention can have negative effects on a large fraction of participants, even though participation is entirely voluntary. This result is consistent with a simple model where time invested in extracurricular programs and time invested in homework represent imperfect substitutes in the education production function.